ANTIMICROBIAL EFFECT OF HYDRO-ALCOHOLIC EXTRACTS OF TRIBULUS TERRESTRIS, PHYLLANTHUS AMARUS AND HEMIDESMUS INDICUS AGAINST COMMON BACTERIAL URINARY PATHOGENS- AN IN VITRO STUDY - Priyadarshini, *Prajna; Pritilata, Panda; Banojini, Parida; Susmita Kumari, Sahu (International Journal of Ayurveda and Pharma Research, 2015)
Context: Urinary tract infection (UTI) is one of the most common infectious diseases in the community. Moreover, with rapidly emerging resistance to antibiotics it is becoming increasingly difficult to treat such infections. Herbal extracts against a wider range of bacterial strains can be used as an efficient herbal drug for UTI. Aims: The primary objective of this study was to detect the in vitro activity of selected Hydro-alcoholic (40:60) extracts of three plants viz. Tribulus terrestris (Drug-1) (fruit extracts), Phyllanthus amarus (Drug-2) (whole plant extracts) and Hemidesmus indicus (Drug-3) (Root extracts) individually and in combination against the isolated bacterial pathogens showing antimicrobial resistance Materials and Methods: This study was conducted for a period of 3 months in the Department of Microbiology. Patients with history of recurrent UTI were included in the study population. Fifty isolates (n=50) showing multidrug resistance isolated from clinical samples are taken for the study Results: The extracts of Tribulus terrestris (Group A), combinations of Tribulus terrestris with Hemidesmus indicus (Group F) and of Tribulus terrestris, Phyllanthus amarus and Hemidesmus indicus (Group G) inhibit both Gram positive and Gram negative bacteria, while Hemidesmus indicus (Groups C) inhibit only Gram positive bacteria. The Gram positive bacteria are more susceptible to these extracts than the Gram negative bacteria. All the herbal extracts tested showed more than 70 % sensitivity to the study group. Conclusions: The hydro-alcoholic extracts of Tribulus terrestris , Phyllanthus amarus and Hemidesmus indicus can be used effectively in the treatment of multi-drug resistant strains causing urinary tract infection. An effective drug could be developed from combination of these herbal extracts which would be natural, more economic and free of any side- effects.